Studi Kuat Tekan Batu Bata Menggunakan Bahan Additive (Abu Sekam Padi, Abu Ampas Tebu dan Fly Ash) Berdasarkan Spesifikasi Standar Nasional Indonesia (SNI) - Abdurrohmansyah, Abdurrohmansyah; Adha, Idharmahadi; Ali, Hadi (Jurnal Rekayasa Sipil dan Desain (JRSDD), 2015)
Brick is one of construction materials of building, shopping complex, real estate etc. Brick is madefrom the mixing of soil and water. In this study, the process of brick production will be tired by mixthe soil with additive materials such as rice husk ash, baggase ash and fly ash. It’s to know howbig the advantage of those additive materials and to compare the compressive strength betweenconventional brick and the brick that have mixed with rice husk ash, baggase ash and fly ash toget Indonesian National Standard for the strong and durable brick.Clay was used as the soil sample in this study. The clay is from Yoso Mulyo Village, Metro. Theadditive materials such as, rice husk ash is from Yoso Mulyo Village Metro, baggase ash is fromPT Indo Lampung Perkasa and the fly ash is from PLTU Tarahan.The result of this study show that the production of brick after burned using additive materialssuch as rice husk ash, baggase ash and fly ash, increase the compressive strength value. So, thestrength of the brick is good enough fulfilled the standard of Indonesian National StandardInstitution.Keywords: Brick, additive fly ash and rice husk ash, baggase ash, compressive strength